2019
DOI: 10.1002/cam4.2089
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 elicited an anti‐Warburg effect through HIF1α/PDK1/PDHA1 to inhibit cholangiocarcinoma tumorigenesis

Abstract: Cholangiocarcinoma (CCA) is an extremely invasive malignancy with late diagnosis and unfavorable prognosis. Surgery and chemotherapy are still not effective in improving outcomes in CCA patients. It is crucial to explore a novel therapeutic target for treating CCA. An NAD‐dependent deacetylase also known as Sirtuin‐3 (SIRT3) has been shown to regulate cellular metabolism in various cancers dynamically. However, the biological function of SIRT3 in CCA remains unclear. In this study, bioinformatics analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…[37] SIRT3 effects mediated by HIF1α/ PDK1/PDHA1 pathway Decrease of SIRT3 expression induced the glycolytic flux through the hypoxia inducible factor α (HIF1α)/PDK1/ PDHA1 axis, promoting CCA progression. [38] Deregulation of PI3K-AKT-mTOR signaling Protein overexpression and activation of PI3K have been associated with tumor progression, differentiation, nodal involvement and reduced OS. Upregulation of activated form of AKT have been reported in neoplastic cells compared to the surrounding normal tissue; Increased mTOR gene copy number and elevated phospho-mTOR levels have been described in biliary cancer specimens in comparison to the adjacent normal or dysplastic epithelium.…”
Section: Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] SIRT3 effects mediated by HIF1α/ PDK1/PDHA1 pathway Decrease of SIRT3 expression induced the glycolytic flux through the hypoxia inducible factor α (HIF1α)/PDK1/ PDHA1 axis, promoting CCA progression. [38] Deregulation of PI3K-AKT-mTOR signaling Protein overexpression and activation of PI3K have been associated with tumor progression, differentiation, nodal involvement and reduced OS. Upregulation of activated form of AKT have been reported in neoplastic cells compared to the surrounding normal tissue; Increased mTOR gene copy number and elevated phospho-mTOR levels have been described in biliary cancer specimens in comparison to the adjacent normal or dysplastic epithelium.…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…The authors showed that in CCA cells, as well as in both tissue samples and in a xenograft model, SIRT3 was downregulated and the glycolysis enhanced. Conversely, the induction of SIRT3 was able to efficiently reduce tumor proliferation via an anti-Warburg effect mediated by the HIF1α/PDK1/PDHA1 pathway [38] (Table 1).…”
Section: Tfr1 High Expressionmentioning
confidence: 99%
“…Furthermore, the authors also confirmed that SIRT3 prevents the Warburg effect in CCA cells and a xenograft mouse model by inhibiting the HIF1α/PDK1/PDHA1 pathway. Collectively, this study suggests that SIRT3 shows anti-Warburg effect activity via regulating the HIF1α/PDK1/PDHA1 pathway and may be a potential therapeutic intervention to impair CCA progression (39).…”
Section: Hif1 Modulate the Cancer Cell Metabolismmentioning
confidence: 70%
“…The first reported target of SIRT3 was acetyl-CoA synthetase 2 (AceCS2) (46), that promotes metastasis formation of renal cell carcinoma (47), however, in gastric cancer, loss of AceCS2 expression predicts poor prognosis (48), which further emphasizes the significance of TME. SIRT3 downregulates HIF1α and pyruvate dehydrogenase kinase 1 (PDK1) in cholangiocarcinoma (49), and suppresses the Warburg effect also by the activation of pyruvate dehydrogenase complex (PDC) and the indirect inhibition of the tumor specific isoenzyme hexokinase II (HK II) (11). SIRT3 regulates fatty acid oxidation via the deacetylation and activation of long chain acyl-CoA dehydrogenase (LCAD) enzyme (50), opposite to HIF1α that suppresses fatty acid oxidation to facilitate cancer progression (51).…”
Section: Epigenetic Background Of Warburg Effect With Emphasis On Sirmentioning
confidence: 99%